logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
0 votes

On putting $y=vx,$ the homogeneous differential equation $x^{2}dy+y(x+y)dx=0$ becomes

\[\begin{array}{1 1}(1)xdv+(2v+v^{2})dx=0&(2)vdx+(2x+x^{2})dv=0\\(3)v^{2}dx-(x+x^{2})dv=0&(4)vdv+(2x+x^{2})dx=0\end{array}\]

Can you answer this question?
 
 

1 Answer

0 votes
$y= vx => \large\frac{dy}{dx} $$=v+x \large\frac{dv}{dx}$
$x^2dy= y(x+y) dx=0$
$x^2 dy =-y (x+y) dx$
$\large\frac{dy}{dx} =-\large\frac{y (x+y)}{x^2}$
$v +x $$\large\frac{dv}{dx} =\frac{-vx(x+vx)}{x^2}$
$x $$ \large\frac{dv}{dx} =\frac{-vx^2(1+v)}{x^2} $$-v$
$x \large\frac{dv}{dx} $$=-v -v^2-v$
$x \large\frac{dv}{dx} $$ =-v^2 -2v$
$x dv= -(v^2-2v)$
$xdv +(v^2 +2v)dx=0$
Hence 1 is the correct answer.
answered May 22, 2014 by meena.p
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...